Transport in an Integrating Europe: Sustainable Development and Cohesion - Roger Vickerman (European Regional Science Association (ERSA), 2003)
The process of European integration, and particularly the enlargement of the EU, has substantial consequences for transport. Transport, and particularly freight transport, has recently been growing faster than GDP. Thus, despite the increasing concerns about the environmental impact of transport and increasing attempts to regulate transport through a more sensitive price mechanism in many countries, what may be termed the transport intensity of the economy has been increasing. This is not just about the impact on traffic levels, but affects the whole relationship between transport and the economy. Changing transport costs impact differentially on different sectors and different regions according not just to the traditional measures of value to weight ratios, but also according to the competitive structure of an industry in a particular location. Increasing transport intensity could be considered a surprising outcome in the first instance. Generally the mass of goods has been falling and the growth of electronic communication could be seen as a substitute for much physical transport. Both of these factors would imply a falling transport content of most production. However, the falling cost of transport may lead to the substitution of transport for other more expensive factors of production. Individuals' preferences for variety see them using cheaper transport as a means of widening access to more destinations. At the same time rising incomes lead to a preference for a greater variety of goods. Given the importance of scale economies in manufacturing production, this implies the need to source these goods from a greater variety of locations, hence the growth of intra-industry trade. Technical advances in transport have reduced transport costs substantially, but in a world of increasing returns firms need to exploit differences in input costs in different locations. The removal of the transport cost constraint on integration may thus lead to an increase in spatial specialisation and concentration which itself induces an increased demand for transport. Understanding these relationships between transport and the economy is critical to achieving a more sustainable European transport system, and to the process of cohesion in the European economy, Attempts to curb transport growth which do not also consider the impact on the structure of production and markets may produce a less sustainable system. On the other hand, moves to ensure the correct pricing of transport services are an essential input to efficient decision making about the optimal location for production and the optimal allocation of resources between different products and services. In this paper we explore some of the dynamics of this system, highlighting the way in which the modelling of the transport system needs to interact with that of the rest of the economy.
Keywords: 330